MOSQUITO LARVICIDAL EFFICACY OF THE ACETONE LEAF EXTRACT OF SOLANUM TRILOBATUM AGAINST CULEX QUINQUEFASCIATUS AND AEDES AEGYPTI - A, Lalitha; S, Thangapandiyan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main objective of our study is to control the vector-borne disease. It is one among the major disease burden in developing countries. There are lots of researches carried out using the various plant extracts against larvicidal activities of the Culex quinquefasciatus and Aedes aegypti. The present investigation was aimed to investigate the phytochemical analysis and mosquito larvicidal activities of Solanum trilobatum in acetone extract against the second instar larvae of C. quinquefasciatus and A. aegypti. Methods: The leaf extract of S. trilobatum was subjected to phytochemical analysis and Gas Chromatography–Mass Spectrometry analysis. The mortality rates of the second instar larvae were recorded after 24, 48, 72, and 96 h of exposure. The lethal concentration (LC)50 and LC90 were determined followed by probit analysis. Results: The LC50 values for C. quinquefasciatus were found to be 265.69 ppm, 227.59 ppm, 212.42 ppm, and 189.47 ppm at various time intervals, and the LC90 values were 558.27 ppm, 504.92 ppm, 479.09 ppm, and 444.28 ppm. Similarly, LC50 values for A. aegypti were noticed at 301.09 ppm, 256.01 ppm, 209.75 ppm, and 167.44 ppm and the LC90 values were 582.34 ppm, 477.52 ppm, 419.40 ppm, and 371.84 ppm for the time interval of 24 h, 48 h, 72 h, and 96 h. Conclusion: The result of the current work revealed that the leaf extract of the S. trilobatum has the potential to be acted as an alternative for the controlling of the mosquitoes.